THE RELATIVE IMPORTANCE OF BUS SYSTEM’S PERCEIVED SERVICE QUALITY (PSQ) ATTRIBUTES AMONG PUBLIC AND PRIVATE MODE USERS IN INDONESIA - Sugiarto, Sugiarto; Fahlevi, Heru; Achmad, Ashfa; Fajri, Lia; Miwa, Tomio (Journal of Applied Engineering Science, 2021)
Importance-Performance Analysis (IPA) is a common approach usually applied in examining public satisfaction and has been adopted in the transportation sector to measure the quality of service provided by the public transport system. This study, therefore, investigated the relative important service quality attributes of bus systems among both public and private modes of transportation users in Banda Aceh in Indonesia. An urban bus system known as the “Trans Koetardja” was used as a case study and a questionnaire designed based on preference survey was applied. A total of 200 samples comprising of 100 bus users and 100 private mode users including cars and motorcycles were used for the preliminary study. Moreover, the IPA approach was used to evaluate the Trans Koetaradja service quality attributes based on importance and performance classification. The quadrant grid plot showed the need for the operators to allocate their resources towards improving their services by considering (a) an improvement in bus stop facilities, (b) enhancement in the route and accurate timetable, and (c) shortening bus travel time and waiting time in the bus stop.
Keywords: service quality, public transport, preference data, IPA, Indonesia